THE INFLUENCE OF PLAYING IN THE PROCESS OF INTERVENTION IN THE TREATMENT OF CHILDREN WITH AUTISTIC SPECTRUM DISORDER - Cristina Bento de Santana Mendonça , Ana; Carlos da Silva, José (Revista Gênero e Interdisciplinaridade, 2022)
The present work, conceived from experiences in the field of therapies, in particular the application of ABA, such as the treatment of children with Autistic Spectrum Disorder (ASD) can be carried out with the help of playful activities, especially games and sound activities. . The search in this work is to present, making use of the literature in this area and relying on studies carried out in this field, how much playfulness can bring benefits to autistic children and the family as an important part in the development process that seeks solutions and treatments that are effective but also present themselves as pleasurable to the child, making them feel motivated to continue with the treatments and, later, understand how, even through play, they could develop.